Investigating the Relationship between Childbirth Type and Breastfeeding Pattern Based on the LATCH Scoring System in Breastfeeding Mothers - Mokhtari Sorkhani, Tayebeh; Namazian, Elahe; Komsari, Samaneh; Arab, Shima (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective The role of breast milk in the physical and mental health of infants and in the prevention of infant death is widely known. The benefits of breastfeeding for mothers and infants have been proven, but several factors can affect breastfeeding. Childbirth is one of the most influential factors. The present study aimed to investigate the effect of the type of delivery (natural childbirth and cesarean section) on breastfeeding based on the latch, audible swallowing, type of nipple, comfort, hold (LATCH) scoring system.Methods The present cross-sectional observational study was performed using the census method among women who referred to Afzalipour Hospital for delivery in May 2020; the breastfeeding pattern was completed by observation and the in-case information, by LATCH checklist. Data were analyzed using the Statistical Package for the Social Sciences (IBM SPSS Statistics for Windows, IBM Corp., Armonk, NY, United States) software, version 19.0, analysis of variance (ANOVA), and the Chi-squared statistical test.Results Out of a total of 254 deliveries (127 natural childbirths and 127 cesarean deliveries), there was no statistically significant difference between the 2 study groups in terms of age, maternal employment status, and infant weight, but there was a statistically significant relationship between the type of delivery, the maternal level of schooling, and the appearance, pulse, grimace, activity, and respiration (Apgar) score in the first minute. The mean score of breastfeeding patterns among the natural childbirth group (9.33) was higher than that of the cesarean section group (7.21).Conclusion The type of delivery affects the mother's performance during breastfeeding, and mothers submitted to cesarean sections need more support and help in breastfeeding.
Keywords: cesarean section; natural childbirth; LATCH; breastfeeding